Mies in Canada: an overview of his projects and works in Toronto and Montreal - Vincenzina La Spina (VLC Arquitectura, 2019)
The main goal of this paper is to show the work of the Modern Movement architect Mies van der Rohe in Canada. A total of 7 projects, 2 of them not implemented and an urban collaboration in the cities of Toronto and Montreal. Most of them are not relatively unknown projects with the exception of the Toronto-Dominion Centre and the Westmount Square in Montreal. These projects were carried out in the 1960s, in his last creative period, when he was over 70. Nevertheless, these projects are unique and iconic, the architect redeveloped and improved solutions and ideas already used in previous projects, and also addressed a different architectural use, the gas station. Mies’s Canadian work adapts his architecture typologies morphologically: high-rise building, pavilion building and the combination of both in complexes paying attention to urban configuration. Consequently, each project is analysed from a historical, typological and compositional perspective, paying attention to its particularities and linking these to other projects by the architect, mainly in the United States.